Using the surgical guide for impression-free digital bite registration in the edentulous maxilla-a technical note - George Michelinakis; Dimitrios Nikolidakis (SpringerOpen, 2019)
Abstract Studies reporting on the application of digital bite registration for fully edentulous patients rehabilitated with dental implants are scarce. This article describes a technique for intraoral digital registration of the occlusal vertical dimension in a fully edentulous maxilla to be rehabilitated with a fixed implant prosthesis. Following fully guided placement of six maxillary implants, the surgical stent duplicating the existing upper full denture was securely fixed on two anterior implants and sectioned along the center line of the hard palate. An intraoral scanner was used for the digital impression of the maxilla and dentate mandible. The occlusal vertical dimension was registered on each side using the contralateral part of the surgical guide along with the scanbodies on each side. The procedure allowed for the precise digital mounting of the digitized jaws. The maxilla was restored with a full-arch implant-supported prosthesis.